2005
DOI: 10.1063/1.2084329
|View full text |Cite
|
Sign up to set email alerts
|

Ex situ ellipsometric investigation of nanocolumns inclination angle of obliquely evaporated silicon thin films

Abstract: We propose an application of spectroscopic ellipsometry pertinent to the characterization of nanostructure inclination of oblique thin films. This technique is employed ex situ in the measurement of silicon thin films fabricated at oblique incidence and modeled as aggregate microstructures formed from amorphous silicon, silicon oxide, and void in the effective medium model. The technique may also be utilized in situ as a powerful probe for the characterization of oblique thin films during their fabrication and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 15 publications
1
44
0
Order By: Relevance
“…Zhang and Zhao 17 theoretically investigated the pitch-height dependent optical extinction spectra of helical Ag nanostructures by the discrete dipole approximation. Approaches were done to model experimental data of straight GaSb nanocones, 18 straight Si nanorods, 19,20 and slanted Si nanocolumns 21 with anisotropic or graded effective medium approximations in order to extract structural properties such as film thickness and porosity, for instance. Among these, only Kaminska et al 19 reported on optical constants in the visible spectral region of their uniaxial straight Si posts with nominal thicknesses ranging from 70 to 1000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Zhao 17 theoretically investigated the pitch-height dependent optical extinction spectra of helical Ag nanostructures by the discrete dipole approximation. Approaches were done to model experimental data of straight GaSb nanocones, 18 straight Si nanorods, 19,20 and slanted Si nanocolumns 21 with anisotropic or graded effective medium approximations in order to extract structural properties such as film thickness and porosity, for instance. Among these, only Kaminska et al 19 reported on optical constants in the visible spectral region of their uniaxial straight Si posts with nominal thicknesses ranging from 70 to 1000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…However, models were limited to uniaxial 6 or orthorhombic descriptions with a maximum of two different constituents. [7][8][9] Recently, we have shown that such an AB-EMA approach also leads to a very good approximation of structural and physical properties of anisotropic Co SCTFs in the THz spectral range. 10 In this letter, we focus on the determination and quantification of a thin conformal Al 2 O 3 layer on top of Co nanocolumns.…”
mentioning
confidence: 99%
“…Particularly noticeable is the absence of the characteristic bulk Ti interband transitions at around = 750 nm. Comparison with results for Si nanocolumns reported by Beydaghyan et al 8 and Hsu et al 15 are of interest. Both groups applied effective medium approximations for rendering a biaxial inhomogeneous material matching their measured GE data with model calculations.…”
Section: ͑1͒mentioning
confidence: 96%
“…This concept, developed for spectroscopic applications, 4-6 was demonstrated for orthorhombic 7,8 and triclinic 9 thin film situations recently. Beydaghyan et al 8 reported on GE measurements of slanted silicon oxide nanoneedles deposited under various deposition angles. Analysis of the ellipsometry data was done under the assumption of homogeneous thin film orthorhombic biaxial properties and validity of the effective medium concept.…”
Section: Monoclinic Optical Constants Birefringence and Dichroism Omentioning
confidence: 99%
See 1 more Smart Citation